Water availability influences thermal safety margins for leaves. (8th July 2021) - Cook, Alicia M.; Berry, Neil; Milner, Kirsty V.; Leigh, Andrea
Abstract: One application of plant physiological heat tolerance measurements is the assessment of vulnerability to increasing environmental temperatures under climatic change. A thermal safety margin (TSM), the difference between physiological tolerance and environmental temperature, is a common metric for the assessment of plant thermal vulnerability. However, there are biological and methodological aspects to consider when evaluating thermal vulnerability that have the potential to substantially alter the assessments. Two such aspects include the leaf to air temperature relationship and the scale at which air temperature data are collected. We grew plants of a desert species, Myoporum montanum, in situ under water‐stressed and well‐watered conditions, and measured their leaf temperatures and photosynthetic heat tolerance ( T 50 threshold) every third day over 12 days in summer. Thermal safety margins were calculated based on leaf temperatures and compared to those calculated with local and regional air temperatures. We found that heat tolerance and the thermal vulnerability assessment of a plant changed with water status. When water was readily available, plants maintained wide leaf temperature safety margins and displayed partial homeothermy. When cooling via transpiration was limited, increasing leaf temperature corresponded with occurrences of leaf poikilo‐ and megathermy, higher heat tolerance and narrower safety margins. Our study shows high physiological heat thresholds are not necessarily reflective of wide safety margins, but instead can indicate a greater vulnerability and increased risk of heat stress exposure. Calculating TSMs using air temperatures can also substantially alter margin widths. Where possible, the use of leaf temperatures in assessments of thermal vulnerability will lead to more meaningful vulnerability assessments. We recommend considering the source and temporal pairing of temperature measurements as well as plant water status, when measuring and interpreting plant TSMs. A free Plain Language Summary can be found within the Supporting Information of this article. Abstract : A free Plain Language Summary can be found within the Supporting Information of this article.